Carcinoid tumor of the ovary: A mysterious puzzle (Indian Journal of Case Reports, 2024)
Carcinoid tumor of the ovary is a rare neoplasm that may present as a solid mass or combined with mucinous tumors or teratomas. Primary ovarian carcinoid represents <0.1% of ovarian malignancies. These tumors are often unilateral presenting as a solid mass and vary from microscopic to very large tumors. Metastatic ovarian carcinoid tumors are seen to be bilateral in most cases. Involvement of the ovary from gastrointestinal carcinoid is rare with no hepatic or peritoneal seedlings. Ovarian carcinoid tumors commonly occur in perimenopausal and postmenopausal women. Surgical removal of the tumor is the standard treatment modality. Tumor size and the presence of metastasis are necessary to plan the treatment modality. We herein report a case of carcinoid tumor of the ovary in a 55-year-old female, which we thought was a dermoid cyst of the ovary and turned out to be carcinoid after detailed immunohistochemical analysis.